L’état des études internationales au Canada : un survol de la recherche scientifique - Abonyi, Arpad; Sylvain, Ivan; Tomlin, Brian (Études internationales, 1978)
This article depicts the configuration of approaches to the scientific study of foreign policy and international politics in Canada, as represented in a systematic survey of research written in Canada and published in forty scholarly journals, some from as early as 1945 up to 1975. Scientific studies found in this sample were analyzed along four dimensions : theoretical basis ; issue area ; units upon which the investigation is based ; and method of analysis. Scientific study of international relations emerged as a largely recent yet growing phenomenon of the last decade. It constitutes a unique subfield outside the mainstream of research, and is concentrated among a relatively small group of individuals and even fewer institutions. Études internationales emerged as the single most important channel of communication for this subfield in Canada